Secular trends in postpartum weight retention from 2003 to 2012: a nationwide, population-based, retrospective, longitudinal study in South Korea - Jong Heon Park; Geum Joon Cho; Yoonjung Yoonie Joo; Sangbum Choi (BMJ Open)
Objective To assess the secular trends in postpartum weight retention (PWR) over a decade with the population-based risk factors.Design Retrospective cohort study.Setting A national health screening examination data provided by the National Health Insurance Service in South Korea.Participants 130 551 women who delivered babies between 1 January 2003 and 31 December 2012 and who underwent a national health screening examination 1 to 2 years prior to delivery and within 1 year after delivery.Methods Their PWR were determined during the study period of 2003–2012. We fitted logistic regression and linear mixed models to assess the independent contribution of PWR to obesity after adjusting for potential confounders.Primary and secondary outcome measures Prepregnancy and postpartum weight and body mass index (BMI).Results The adjusted PWR increased from mean value of 2.02 kg in 2003 (95% CI 1.88 to 2.15) to 2.79 kg in 2012 (95% CI 2.73 to 2.84) (p value for trend <0.01), after adjusting potential confounders including age, prepregnancy time, postpartum time, prepregnancy BMI, income and smoking status. The risk for a PWR of more than 5 kg also increased over the study period.Conclusions Secular increases in PWR have been significantly observed between 2003 and 2012 for childbearing women. It is necessary to identify risk factors contributing to the observed increase and develop effective strategies to address the heightened risk for PWR.